Social Inequalities in Climate Change-Attributed Impacts of Hurricane Harvey - Kevin T. Smiley; Ilan Noy; Michael Wehner; Dave Frame; Christopher Sampson; Oliver E. Wing (Center for Economic Studies and ifo Institute (CESifo), 2021)
Climate change is already increasing the severity of extreme weather events such as with rainfall during hurricanes. But no research to date investigates if, and to what extent, there are social inequalities in current climate change-attributed flood impacts. Here, we use climate change attribution science paired with hydrological flood models to estimate climate change-attributed flood depths and damages during Hurricane Harvey in Harris County, Texas. We then combine this information with detailed land-parcel and census tract socio-economic data to describe the socio-spatial characteristics of these climate change-induced impacts. Our findings show that 30 to 50% of the flooded properties would not have flooded without climate change. These climate change-attributed impacts were particularly felt in Latinx neighborhoods, and especially so in Latinx neighborhoods that were low-income and among those located outside of FEMA's 100-year floodplain (and therefore less likely to be insured). An important implication is the need to focus on pressing climate justice challenges that not only concern future climate change-induced risks, but are already affecting vulnerable populations disproportionately now.
Keywords: Q54; 330; Hurricane Harvey; attribution; climate change; poverty; flood insurance